Formulation and In Vitro Evaluation of Ufasomes for Dermal Administration of Methotrexate. (12th June 2012) - Sharma, Arvind; Arora, Sandeep
Abstract : Dermal drug delivery system that is required to localizes methotrexate (MTX) in the synovial joint is needed to treat inflammation in rheumatoid arthritis (RA). The present investigation aims at exploring the potential of fatty acid vesicles for the topical delivery of methotrexate. Vesicles were prepared by film hydration method using oleic acid as a fatty acid principal component. Developed vesicles were characterized for size, size distribution, shape, in vitro release, pH dependent, and storage stability. Interaction between MTX and oleic acid was investigated using differential scanning calorimetry. The MTX amount permeated through rat skin was three- to fourfold higher using oleic acid compared to those from plain drug solution or carbopol gel. At the end of the skin permeation assay using ufasomes, up to 50% of the administered dose was found in the skin. These results suggest that methotrexate encapsulated in oleic acid vesicles may be of value for the topical administration of MTX in the treatment of psoriasis.